Using technology and tailored feedback to improve dietary behaviours - Shoneye, Charlene Lisa (Curtin University, 2020)
Together, poor diet and obesity are the leading cause of chronic disease in Australia. Digital interventions that can be delivered remotely and up-scaled have the potential to improve diet quality and produce modest weight loss at a population level. This thesis details the studies undertaken to design and evaluate a theory driven, digital tailored weight loss intervention.Findings from this body of work present evidence regarding the acceptability and feasibility of using technology to improve dietary intake among adults with overweight and obesity.